2020
DOI: 10.3390/ijms21082672
|View full text |Cite
|
Sign up to set email alerts
|

Tat-Biliverdin Reductase A Exerts a Protective Role in Oxidative Stress-Induced Hippocampal Neuronal Cell Damage by Regulating the Apoptosis and MAPK Signaling

Abstract: Reactive oxygen species (ROS) is major risk factor in neuronal diseases including ischemia. Although biliverdin reductase A (BLVRA) plays a pivotal role in cell survival via its antioxidant function, its role in hippocampal neuronal (HT-22) cells and animal ischemic injury is not clearly understood yet. In this study, the effects of transducible fusion protein Tat-BLVRA on H2O2-induced HT-22 cell death and in an animal ischemia model were investigated. Transduced Tat-BLVRA markedly inhibited cell death, DNA fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Neuroblastoma cells lacking BVR-A are unable to activate the Akt/GSK3β axis, thus appearing more susceptible to H 2 O 2 -induced oxidative damage [21]. Furthermore, induction of BVR-A was reported to prevent hippocampal cell death by inhibiting DNA fragmentation and generation of reactive oxygen species in an ischemic model [22].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroblastoma cells lacking BVR-A are unable to activate the Akt/GSK3β axis, thus appearing more susceptible to H 2 O 2 -induced oxidative damage [21]. Furthermore, induction of BVR-A was reported to prevent hippocampal cell death by inhibiting DNA fragmentation and generation of reactive oxygen species in an ischemic model [22].…”
Section: Introductionmentioning
confidence: 99%
“…Also, GK2-BLVRA protein increased Caspase-9 and -3 expressions, whereas expression of cleaved Caspase-9 and -3 protein decreased under the same conditions. We have reported that Tat-BLVRA protein increased Caspase-8, -9 and -3 expression levels in H 2 O 2 -exposed HT-22 cells [30] and other studies have shown that biliverdin reductase enhanced cell survival by inhibiting death receptor-5, cytochrome c or caspase-3 activity [52,53]. Our results are consistent with the study by Song et al [54] in which they have shown that biliverdin reductase prevented apoptosis of pulmonary arterial smooth muscle cell (PASMC) by inhibiting mitochondrial dysfunction and increasing Bcl-2, Caspase-9 and -3 expressions in the cells.…”
Section: Discussionmentioning
confidence: 81%
“…Thus PTDs have been applied as effective vehicles to deliver therapeutic molecules like protein, DNA, RNA, liposome and nanoparticles into cells because they have the ability to transduce into cells [21,22]. Among them, Tat-PTD derived from the human immunodeficiency virus is widely used to deliver the therapeutic protein into cells [23][24][25], and many groups have shown that Tat-fusion protein is transduced into a variety of cells, which were markedly protected against oxidative stress-induced cell death [26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Gene ontology term analysis ( Figure 4 A) showed that these genes were enriched in oxidative stress–related terms, including tissue development ( Monteiro et al., 2017 ), negative regulation of cell differentiation ( Chen et al., 2018 ) keratinocyte proliferation ( Smirnov et al., 2016 ), and positive regulation of cell cycle ( Baeeri et al., 2019 ). And the KEGG analysis determined that these differentially expressed genes were mostly enriched in pathways such as the transforming growth factor-beta signaling pathway, focal adhesion, the Wnt signaling pathway, regulation of the actin cytoskeleton, and the MAPK signaling pathway, which were implicated in oxidative stress ( Farah et al., 2011 ; Lu et al., 2011 ; Lou et al., 2018 ; Zhang et al., 2018b ; Kim et al., 2020 ) ( Figure 4 B).
Figure 4 GO and KEGG enrichment analysis of Cd-induced differentially expressed genes.
…”
Section: Resultsmentioning
confidence: 99%